Frequency, severity, and factors associated with clinically significant drug‑drug interactions among patients with cancer attending Mbarara Regional Referral Hospital Cancer Unit, Uganda - Luzze, Bonny; Atwiine, Barnabas; Lugobe, Henry Mark; Yadesa, Tadele Mekuriya (BMC cancer, 2022)
Background: Cancer is a major public health problem with pharmacotherapy being the cornerstone of its management. Cancer patients receive multiple drugs concurrently risking Drug-Drug Interactions (DDIs). DDIs, though avoidable, can significantly contribute to morbidity, mortality, and increased healthcare costs in this population of patients. Currently, there is no published study from Uganda on clinically significant DDIs (cs-DDIs) among cancer patients. This study identifies frequency, severity, and factors associated with cs-DDIs at Mbarara Regional Referral Hospital Cancer Unit (MRRHCU). Method: A cross-sectional study was conducted among 300 cancer patients receiving chemotherapy from a tertiary care hospital in western Uganda from January–February 2022. A questionnaire and data collection form were used to collect patient data. Lexicomp® Drug interaction software was used to screen the patient drug information for DDIs and assess their severity. Predictors of DDIs were identified using logistic regression using SPSS (Statistical Package for Social Sciences). Result: Three hundred participants were enrolled with a mean age of 48 } 23.3 years. One hundred eighty-one patients experienced 495 cs-DDIs; with a mean of 1.7 } 2.2. The prevalence of cs-DDI was 60.3% (55.0-66.0% at 95% CI). Digestive organ neoplasms were the most commonly (80, 26.7%) diagnosed category, and ‘plant alkaloids and other natural products were the most frequently (143, 47.7%) used chemotherapeutic drug classes. About three quarters of cs-DDIs were rated as category C risk (367, 74.1%) whereas over two-thirds (355, 71.7%) were moderate in severity. Being female (aOR = 2.43 [1.23–4.48 at 95% CI]; P-value = 0.011) and use of ≥ 6 drugs concurrently (aOR = 18.82 [9.58–36.95 at 95% CI]; P-value < 0.001)) were significantly associated with cs-DDIs. Conclusion: More than half of the participants experienced at-least one cs-DDI which is generally higher than what was reported in high-income settings. About three-quarters were category C and moderate in severity, and require enhanced monitoring for safety and treatment outcome. Being female and using ≥ 6 drugs were significantly associated with cs-DDIs.
Keywords: Frequency; Factors associated; Drug-drug interactions; Cancer